Problems of Monitoring and Prediction of Possible Emergency Situations on the Territory of Uzbekistan and the Ways of their Solution - Nazarkulovich, Khodjakulov Mukhtorzhon (European Journal of Life Safety and Stability (2660-9630), 2022)
The purpose of the scientific research is to protect the population and territories of the Andijan region through the implementation of preventive measures to prevent emergencies of a natural and man – made emergencies. The task of the work is to develop specific, scientifically based recommendations for further improvement of the system for monitoring and forecasting emergency situations